The factors of employee innovation on organization success at SPRM Negeri Pahang / Nurmala A. Hassan - A. Hassan, Nurmala (2016)
In this study I will conduct a research about The Factors of Employee Innovation on Organization Success at SPRM Negeri Pahang. Starting with finding and the respondent that contribute in my research will started on 29th February 2016 and end on 19th June 2016. All the input from this research had related to environment in the organization and also I had identified the problem that have in the organization and also after this research finish and had proposed the solution from the problem to the organization. The main objectives of this study are to investigate the relationship of factors employee innovation on the organization success. Besides that, the objective is to identify the most effective factor of employee innovation that contributes the most to organizational success. The data analysis had proven that SPRM Negeri Pahang has the ability to diversify, by the significant relationship between leadership, organization support and empowerment toward to organization success. Any changes found in leadership, organization support and empowerment are significant to the changes of organization success of SPRM Negeri Pahang. Finally, it was recommended for this organization to upgrade their independent variable by using more effective in order to increase organization success.